Pilgrim Tourist Service Practices at Muarajambi Temple - Dian Anita Sari; Johannes Johannes; Raja Sharah Fatricia (Journal of Accounting, Management, and Economics Research (JAMER), 2026)
This study analyzes service practices for pilgrim tourists in the Muaro Jambi Temple area as a cultural heritage-based religious tourism destination. A qualitative approach was employed, using interviews, observation, and documentation. Data were analyzed through the Miles and Huberman Model alongside the 4A framework: attraction, accessibility, amenities, and ancillary services. The findings indicate that service practices have been implemented relatively well, supported by three main patterns: informative, mentoring, and facilitative. The area’s primary attraction lies in its historical and spiritual significance as a former center of Buddhist learning. Accessibility is generally adequate, although internal circulation requires improvement. Basic amenities are available but have not fully supported the spiritual needs of pilgrims. Ancillary services remain largely community-based and lack institutional integration. The study also identifies a pattern of devotional loyalty among the global Buddhist community, reflected in repeat visitation driven by strong spiritual attachment. Strengthening spiritually oriented services and integrated management is therefore essential for sustainable pilgrim tourism development. These findings contribute to a service quality framework tailored to heritage-based religious tourism contexts.